Rational Control of GeSn Nanowires. Issue 5 (10th January 2022) - Gong, Ruiling; Zheng, Lulu; Roca i Cabarrocas, Pere; Chen, Wanghua
Abstract : Research on Si compatible direct bandgap semiconductors is a hot topic due to the high demand of Si compatible optoelectronics. The group IV compounds, namely GeSn, has been studied extensively in its different forms: thin films, nanowires (NWs), and nanocrystals. Importantly, the attention being paid to GeSn NWs has increased in recent years thanks to two key factors: 1) better crystalline quality due to an easier strain relaxation in NWs; and 2) extraordinary Sn content (up to 30 at.%) associated to a very fast NW growth (>20 nm s −1 ). Therefore, to effectively control the growth of GeSn NWs is a key issue for a practical application. Herein, various control aspects including the nature of the catalysts, the morphology of the NWs, and their Sn content are presented. Abstract : GeSn nanowires can be synthesized via top‐down and bottom‐up approaches. Top‐down involves growing GeSn layers on a Ge buffer layer and combining wet etching with selective dry etching to achieve strain‐free GeSn nanowires. Bottom‐up methods include i) vapor–liquid–solid processes via chemical vapor deposition and molecular beam epitaxy, ii) plasma‐assisted in‐plane solid–liquid–solid growth, and iii) solution‐based mechanisms.